Penguatan Kepedulian Lingkungan melalui Kegiatan Penanaman Bibit di Dusun Bendrong - Fillah Anjany; Nabila Farida Farah; Vira Riskyana Alya Ramadhani; Sya’roni Sya’roni; Fahmy Eka Wahyu Ferdiansyah; Wahyu Harianto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The community service program in Dusun Bendrong aimed to foster environmental awareness through the planting of timber and fruit seedlings as a response to declining forest quality and reduced water availability caused by vegetation loss. This program sought to enhance community participation in forest conservation while strengthening local wisdom related to environmental stewardship. The activity was conducted in three stages: pre-activity observation and coordination with the Village Head and community leaders, joint planting of 14 seedlings by Student Community Service (KKM) participants and local residents, and monitoring and evaluation to assess implementation and participant understanding. The results showed that all seedlings were successfully planted, with high levels of participation from both students and community members. The activity increased awareness of forest conservation and highlighted the importance of collective action in maintaining environmental sustainability. Timber trees contributed to forest restoration, improved water absorption, and reduced erosion risk, while fruit trees provided additional economic and social benefits for the community. Overall, this participatory approach proved effective as a sustainable model for community service programs that integrate environmental conservation and community empowerment.